THE DEPLOYMENT OF REVENUE CYCLE ACCOUNTING INFORMATION SYSTEM IN THE SERVICE BUSINESSES OWNED BY THE REGIONAL GOVERNMENT OF WEST NUSA TENGGARA PROVINCE - Rafa Karimah; Izzari Amperaningrum; Ninuk Wiliani (LPPM Nusa Mandiri, 2021)
Based on Law Number 25/2009 on Public Services, the West Nusa Tenggara Government established Wisma NTB. However, the lack of interest from the government to stay at Wisma NTB while they are in Jakarta is the main cause of the inability of the NTB Liaison Agency to reach its local revenue target. In connection with the reason and the latest technological development, information systems are urgently needed by the agency to assist its operational and decision-making activities. This study aims to determine the current income cycle provided at Wisma NTB, to evaluate the effectiveness and efficiency of the ongoing cycle, and to determine whether or not to develop the available system. The research methods used for data compilation consisted of field observations, interviews, and literature studies. The system development method used is Extreme Programming (XP), software development procedures launched through practical principles and techniques. Meanwhile, the internal control evaluation applies COSO. The results reveal the prevailing control system has been proper and in line with prevailing environmental control and monitoring standards. However, weaknesses can be found in control, risk assessment, information, and communication activities. The elements are related to technology because the current income cycle worked less than optimal. Thus, it is necessary to develop the system. The developments include the provision of a room reservation system, a payment gateway system, and a system for recording online transactions so such transactions can be accessed anytime, anywhere.